Evaluating the Serum Level of IL-40 in a Sample of Iraqi Men with Ankylosing Spondylitis - Ahmed, Shahad S.; Abed, Reema M. (Iraqi Journal of Science, 2024)
Ankylosing spondylitis (AS) is a form of arthritis that predominantly affects the spine and is characterized by immune and skeletal disorders causing deterioration in structural integrity, functional capability, and overall quality of life. This study aimed to estimate IL-40 serum level in Iraqi men who had AS. Blood samples were obtained from 100 patients (with AS) and 100 men (controls group). The enzyme-linked immune sorbent assay was used to measure the IL-40 level in blood samples. The investigation’s findings showed that the typical patient’s age was 40.56 ± 10.19 years old. While the control group’s average age was 38.76 ± 10.52 years. The results found that the duration of the disease was< 5 years in 44% of cases, 5-10 years in 50% and >10 years in 6% of cases. Patients without HLA-B27 had higher IL-40 levels, on average than those with HLA-B27 (p= 0.0001). Analysis of the receiver operating characteristic (ROC) curve suggested that a serum IL-40 level of 14.18 pg/mL (AUC = 0.93; p= 0.0001) was optimal which was considered the point at which a person was either affected or not. The differences in the interleukin level in serum between patients and controls were included. The results for levels of IL-40 appeared higher significant differences in patients as contrasted to healthy controls (19.10 ± 5.07 vs 9.13 ± 4.03 pg/ml; p<0.001). Also, the results showed that IL-40 was not substantially correlated with BASFI, BASDAI, Erythrocyte sedimentation, white blood cell count, disease duration, hemoglobin, urea, C-reactive protein or creatinine. While age had a significant positive association with IL-40 serum levels. In conclusion, IL-40 levels in the serum of AS patients were significantly higher than those of healthy controls which indicated that it could play an important pathogenetic role in AS.